2018
DOI: 10.21083/ajote.v7i1.3904
|View full text |Cite
|
Sign up to set email alerts
|

Science Curiosity as a Correlate of Academic Performance in Mathematics Education: Insights from Nigerian Higher Education

Abstract: This study investigated the relationship between the science curiosity levels of undergraduate of mathematics education in a Nigerian higher educational institution and their academic grade point averages. The study employed a correlational survey research design on a random sample of 104 mathematics education students. The Science Curiosity Scale -Comparative Self Report was adapted to measure the students' distinctive appetite for consuming science-related media for personal edification. The correlational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…The study revealed that curiosity improves students' and, as well, predicts higher academic performance. The current study's findings, on the other hand, contradicted those of Abakpa et al [23]. They found a weak negative relationship between curiosity and academic performance among students, indicating that curiosity did not predict students' academic performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study revealed that curiosity improves students' and, as well, predicts higher academic performance. The current study's findings, on the other hand, contradicted those of Abakpa et al [23]. They found a weak negative relationship between curiosity and academic performance among students, indicating that curiosity did not predict students' academic performance.…”
Section: Discussioncontrasting
confidence: 99%
“…In this particular study, both interest-specific epistemic curiosity and deprivation-specific epistemic curiosity significantly and positively predicted the academic performance of students. A study conducted in Nigeria by Abakpa et al [23] revealed a weak and negative relationship between curiosity and academic performance in students.…”
Section: Curiosity As a Predictor Of Academic Performance Of Studentsmentioning
confidence: 99%
“…It accurately describes the problem and experiences. Phenomenology has been widely used in educational research to gather experiences, views, and beliefs regarding teaching-learning, curriculum, pedagogical approaches and school environment (Abakpa, Agbo-Egwu, & Abah., 2017). Hence the students' experiences, and emotions while learning in mathematics classrooms can be well understood using a phenomenological lens.…”
Section: Methodsmentioning
confidence: 99%
“…Naturalist intelligence has no significant effect on students' critical thinking skills and curiosity [29]. Abakpa et al [66] showed that scientific curiosity and academic performance were negatively correlated.…”
Section: Introductionmentioning
confidence: 99%